Update on Surgical Techniques Best Practices to Optimize Outcomes Following Gel Stent Implantation - Vera V; Sheybani A; Panarelli JF; Grover DS; Lee J; Craven ER; Samuelson TW; Ahmed IIK (Clinical Ophthalmology)
Vanessa Vera,1 Arsham Sheybani,2 Joseph F Panarelli,3 Davinder S Grover,4 James Lee,5 Earl Randy Craven,2 Thomas W Samuelson,6 Iqbal Ike K Ahmed7 1Allergan, an AbbVie company, Irvine, CA, USA; 2Washington University School of Medicine, St Louis, MO, USA; 3Department of Ophthalmology, New York University Langone Health, New York, NY, USA; 4Glaucoma Associates of Texas, Dallas, TX, USA; 5Colorado Eye Institute, Colorado Springs, CO, USA; 6Minnesota Eye Consultants, University of Minnesota, Minneapolis, MN, USA; 7John Moran Eye Center, University of Utah, Salt Lake City, UT, USACorrespondence: James Lee, Colorado Eye Institute, Colorado Springs, CO, 80924, USA, Email jlee@eyescolorado.comAbstract: The XEN® 45 Glaucoma Treatment System (gel stent; Allergan, an AbbVie company, Irvine, CA, USA) is a minimally invasive bleb-forming surgical device that was originally approved to lower intraocular pressure by diverting the aqueous humor from the anterior chamber to the subconjunctival space (like trabeculectomy) following ab-interno placement. Since approval of the gel stent in multiple countries, the implantation technique has evolved considerably, being performed ab interno or ab externo with open or closed conjunctiva, based on patients’ needs and/or surgeons’ preferences. Additional technical variations that can facilitate gel stent placement and/or improve outcomes have also emerged. This article aims to increase awareness of these developments to facilitate informed decision-making and improve surgical success and outcomes for patients.Keywords: ab interno, ab externo, glaucoma, intraocular pressure, surgical outcomes, XEN